Multifunctional Roles of Plant Cuticle During Plant-Pathogen Interactions - Ziv, Carmit; Zhao, Zhenzhen; Gao, Yu G.; Xia, Ye (Frontiers in Plant Science, 2018)
In land plants the cuticle is the outermost layer interacting with the environment. This lipophilic layer comprises the polyester cutin embedded in cuticular wax; and it forms a physical barrier to protect plants from desiccation as well as from diverse biotic and abiotic stresses. However, the cuticle is not merely a passive, mechanical shield. The increasing research on plant leaves has addressed the active roles of the plant cuticle in both local and systemic resistance against a variety of plant pathogens. Moreover, the fruit cuticle also serves as an important determinant of fruit defense and quality. It shares features with those of vegetative organs, but also exhibits specific characteristics, the functions of which gain increasing attention in recent years. This review describes multiple roles of plant cuticle during plant-pathogen interactions and its responses to both leaf and fruit pathogens. These include the dynamic changes of plant cuticle during pathogen infection; the crosstalk of cuticle with plant cell wall and diverse hormone signaling pathways for plant disease resistance; and the major biochemical, molecular, and cellular mechanisms that underlie the roles of cuticle during plant-pathogen interactions. Although research developments in the field have greatly advanced our understanding of the roles of plant cuticle in plant defense, there still remain large gaps in our knowledge. Therefore, the challenges thus presented, and future directions of research also are discussed in this review.